A Double-Selective Tissue Culture System for Isolation of Wild-Type Poliovirus from Sewage Applied in a Long-Term Environmental Surveillance - Manor, Y. (American Society for Microbiology, 1999)
We describe a simple, cost-efficient, double-selective method for isolation of wild-type poliovirus from sewage samples containing vaccine polioviruses and other enteroviruses, with a detection limit of 18 to 50 PFU per 1 to 2 liters of sewage. By this method we were able to process 1,700 sewage samples collected between 1991 and 1996, from which 10,472 plaques were isolated, 41 of them being identified as wild-type polioviruses.